Look up with me Neil deGrasse Tyson : a life among the stars - Berne, Jennifer
"A biography of famed astrophysicist Neil deGrasse Tyson and awe-inspiring facts about our universe"...
Keywords: Tyson, Neil deGrasse; Astrophysicists -- United States -- Biography; Astronomy -- Juvenile literature; Bilderbuch; Sachbilderbuch